Seismic Response of a Cable-Stayed Bridge with Concrete-Filled Steel Tube (CFST) Pylons Equipped with the Seesaw System - Panagiota Katsimpini; George Papagiannopoulos; George Hatzigeorgiou (GeoHazards)
This research examines the seismic behavior of a cable-stayed bridge featuring concrete-filled steel tube (CFST) pylons, which includes the seesaw system. The objective of the study is to assess the efficacy of the seesaw system in mitigating the seismic response of the bridge across various earthquake scenarios, while also accounting for the implications of soil–structure interaction (SSI). A comprehensive finite element model of the bridge is constructed, incorporating the CFST pylons, cable system, and the novel seesaw energy dissipation system. This model is tested against a range of ground motions that reflect different seismic hazard levels and characteristics. The impact of SSI is analyzed through a series of parametric studies that explore various soil conditions and foundation types. The findings indicate that the implementation of the seesaw system markedly decreases the seismic demands placed on the bridge structure, particularly regarding deck displacements, pylon base shear, and cable forces. Furthermore, the study underscores the significant influence of SSI on the dynamic behavior of the bridge system, emphasizing the necessity of its inclusion in seismic design and analysis. This research enhances the understanding of seismic protection strategies for cable-stayed bridges, providing valuable insights into the advantages of integrating energy dissipation systems and recognizing the importance of SSI effects in evaluating seismic performance.